Analisis Penerapan Model AIDA dalam Komunikasi Pemasaran Produk Kayu di UD Rahmat Jati Melalui Facebook - Sahri Aflah Ramadiansyah; Bramantio Firdausy (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
Social media has become a primary marketing channel for small and medium enterprises (SMEs). UD Rahmat Jati, a woodcraft business in Ketewel, Bali, utilizes Facebook Marketplace to promote its teakwood products. This study aims to understand how the AIDA model (Attention, Interest, Desire, Action) is applied in the company’s digital marketing communication and how consumers respond to these strategies. The research employs a descriptive qualitative approach with a single case study. Data were collected through in-depth interviews with the business owner, direct observation of digital marketing activities, and content analysis of 20 Facebook Marketplace posts uploaded between January and June 2025. The findings show that the elements of Attention and Interest are relatively strong, reflected in the use of product visuals and basic product information. However, the Desire and Action stages remain weak due to the absence of emotional storytelling, customer testimonials, and clear call-to-action messages in most posts. As a result, online engagement increases but does not translate into significant purchase conversions. The study concludes that partial implementation of the AIDA model improves consumer awareness, yet strengthening the Desire and Action stages is essential for digital communication to effectively drive sales. These findings may serve as a reference for other SMEs seeking to optimize social media-based marketing strategies.